Perancangan Website Pembelajaran Sederhana Untuk Anak Sekolah Dasar - Kristianti, Novera; Kristiani, Margareta (Journal of Information Technology and Computer Science, 2022)
Indonesia is included in a country with a fairly high birth rate, so many young people in Indonesia have a low level of education. Education is very important for every individual in developing potential and creativity, as well as being a responsible person. In addition to formal and non-formal education, informal education obtained in the family or surrounding environment also has an important role in the formation of individual character. However, the coronavirus pandemic is a factor in children's lack of interest in learning. Therefore, the use of the web as an interesting learning medium can help children in learning online at home. Currently, mobile phones are common devices owned by children, but often used only to play games. To overcome this, the author decided to create a simple learning website for elementary school children that can be accessed anytime and anywhere. This website has the title "Simple Learning Website for Elementary School Children" and is expected to have a positive impact on children in the learning process.